Relatório de Estágio Profissional "O percurso para a docência de uma Estudante-Estagiária: do sonho à realidade" - Inês Soares Rodrigues dos Santos (2019)
In the context of teacher education, the school placement is crucial because it provides the opportunity to experience the teacher occupation. The present document witnesses the path of a preservice teacher (the author) and takes place in a school in Vila Nova de Gaia, in a group composed by three preservice teachers, an University supervisor and a cooperating teacher of the school. Throughout the document will be presented strategies applied and the difficulties felt in the pedagogical practice. It will also be presented the relationships developed in the school environment and the involvement in the school activities. All decisions taken were focused on the students' teaching-learning process and preservice teacher professional growth in teaching functions. This document also includes a study on a theme that emerged at the beginning of the school year - the Active School concept - focused on the characterization of the cooperative school's physical spaces and potential improvement strategies to increase the physical activity levels of students. The writing of this document represented a fundamental mark in the reflexive road of the preservice teacher, because it enabled her to enrich herself both in professional and personal level.